Pathological Effects of Apalutamide in Lower-risk Prostate Cancer: Results From a Phase II Clinical Trial. Issue 2 (1st February 2023) - Schweizer, Michael T.; True, Lawrence; Gulati, Roman; Zhao, Yibai; Ellis, William; Schade, George; Montgomery, Bruce; Goyal, Sonia; Nega, Katie; Hakansson, Alexander K.; Liu, Yang; Davicioni, Elai; et al.
Abstract : Purpose: Active surveillance is a safe and effective strategy for men with lower-risk prostate cancer who want to avoid local therapy; however, many patients on active surveillance progress to active treatment (eg, prostatectomy or radiation). We hypothesized that apalutamide would decrease active surveillance attrition rates through downstaging low-grade tumors. Materials and Methods: This was an open-label, single-arm, phase II study testing 90 days of oral apalutamide 240 mg daily in men with low- to intermediate-risk prostate cancer on active surveillance. The primary objective was to determine the percentage of patients with a negative biopsy immediately following treatment. Secondary objectives were to assess long-term clinical outcomes, quality of life, safety, and biomarkers of response/resistance. Results: Twenty-three patients enrolled and 22 completed 90 days of apalutamide with post-treatment biopsy. Fifteen (65%) had Grade Group 1 disease, and all others had Grade Group 2 disease. Seven (30%) had favorable- to intermediate-risk disease. Of 22 evaluable patients, 13 (59%) had no residual cancer on post-treatment biopsy. The median time to first positive biopsy was 364 days (95% CI: 91-742 days). The impact of apalutamide on quality of life was minimal and transient. Decipher risk classifier revealed a greater number of negative post-treatment biopsies in those with higher baseline genomic risk score ( P = .01). Conclusions: The negative repeat biopsy rate following 90 days of apalutamide was high in men with prostate cancer followed on active surveillance. Apalutamide was safe, well tolerated, and had minimal impact on quality of life. Randomized studies evaluating the effects of apalutamide in men enrolled on active surveillance are warranted.